Approaches in Teaching Grammar at SMA Negeri 1 Sumberlawang in 2015/2016 Academic Year - Azizah, Nur, Aryati Prasetyarini S.Pd, M.Pd (2017)
Nur Azizah. A 320 120 076. APPROACHES IN TEACHING GRAMMAR AT SMA NEGERI 1 SUMBERLAWANG IN 2015/2016 ACADMIC YEAR. Research Paper. Muhammadiyah University of Surakarta. 2016. This research is aiming on 1) describing the approach adopted by the teacher in teaching English grammar at SMA Negeri 1 Sumberlawang 2) describing the procedure of the approach adopted in teaching English grammar at SMA Negeri 1 Sumberlawang. In this research, the researcher applied a descriptive qualitative research as the type of the research. The object of the study is approaches applied by the teacher, deductive or inductive approach and the procedure of each approach. The data of the study are taken from informant, event, and document. The technique of collecting data is through interview, observation, and document analysis. The technique for analyzing the data is through 1) assembling the data 2) coding the data 3) comparing the data 4) building interpretations and 5) reporting the outcomes.The result of this study shows that 1) The approach adopted by the teacher in teaching English grammar at SMA Negeri 1 Sumberlawang in 2015/2016 academic year is inductive and deductive approach in which the first approach applied by the teacher is inductive by presenting examples first then drawing conclusion by those examples and then followed by deductive approach with presenting further explanation of the material and then giving more examples continuously in every teaching learning process. 2) The whole procedures of the approach adopted by the teacher in teaching English grammar at SMA Negeri 1 Sumberlawang consist of three points, namely opening, whilst of teaching, and closing, in which in whilst of teaching, it consists of two main approaches, inductive and deductive approach. 3) The teaching grammar principles of the teacher does not meet all of the principles because the teacher still focuses on the declarative knowledge rather than procedural knowledge. However, the teaching learning process is fun, joyful, and interesting for the students.